En studie om ämnet resurssatt tidsplanering, uppföljning och arbetsförändring. : Samt framtagandet av en mall och instruktion för projekttidplaner och dess uppföljning i MS Project, på uppdrag av BDX Företagen AB. - Johansson, Marie (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2021)
The planning, development and updating of the construction project are key elements for leading a project to the finish line. A programme adapted to implementation is also required to obtain the best results. The two most common work programs for creating project schedules are Microsoft Excel and Microsoft Project. A project's tasks are identified and structured in a schedule, often called Gantt Schedule. It should give employees at the workplace an idea of the ongoing project's activities, as well as upcoming important events and deadlines. A timeschedule should also be able to pare for changes and allocate the project's resources evenly to prevent congestion. An effective schedule includes project start and finish dates, needed resources, and recurring tasks for updating and monitoring the project schedule. An assignment issued by BDX Företagen AB gave me the opportunity to create a template and instruction for facilitated work on the development and updating of project schedules in Microsoft Project. BDX is a construction company primarily active in northern Sweden. They carry out assignments for both private individuals and companies in land, road and infrastructure. They work daily on the creation of ongoing and upcoming projects and use Microsoft Excel as a planning program. The background to the assignment of BDX is their efforts to improve work primarily on updating a project's schedule with the transition from Microsoft Excel to Microsoft Project. The template created contains the basic settings required for a good structure for a schedule. It also includes notes and shorter explanations of tools and features. BDX's focus on improvement around updating provided the premise that the template also contains recurring tasks, which means that they are scheduled continuously during the project. The usage instruction provides a more detailed description of the template, basic settings, and features.